About the Evaluations of the Environmental Protection Activities’ Effectiveness - Michail Michailov (Studia Ecologiae et Bioethicae)
A few contemporary examples can be found in various publications to provoke a more profound reflection on the assessment of environmental action. Whatever methodology is used to determine the importance of all types of environmental activities and assess their effectiveness, specific approaches must be adopted. It is crucial to understand that “environmental activities” are not just an appendage to the science of “ecology.” They also represent a specific period in the development of the world, in the second part of the 20th century, during which specific assessments of the effectiveness of human activities are necessarily provided. The science of ecology usually deals with such concepts as biotic, abiotic, and anthropogenic factors. They should account for the specific conditions, impacts, and effects on ecosystems. However, such concepts are also used in other disciplines, which have interests in this field. Therefore, the material in this article will address some critical issues connected to the assessment of the effectiveness of environmental actions.